Factors Influencing on Entrepreneurial Behavior of Street Vendors (A Case in Pekanbaru City, Riau Province) - Marliati, Marliati (Universitas Muhammadiyah Yogyakarta, 2020)
One of the informal sectors that happening in urban areas is ‘pedagang kaki lima' (PKL) known for its contribution to reduce unemployment despite their existence are often raise urban planning problems. However, PKL should be given the opportunities by the government to increase their economic empowerment and competitiveness. The purpose of this study is to analyze personal characteristics and business profiles; family environment, internal and external environment of the business; and its influence on PKL entrepreneurial behavior. The research was conducted in Pekanbaru from March to December 2019. Respondents of the study are PKL street food totaling 131 people. The data is analyzed by using the Partial Least Square (PLS) method. The results showed that the average personal characteristics of PKL aged 36.93 years, level of education equivalent to high school with 5.27 years of business experience and average net income per day is Rp. 442,404 which 52.7 percent do not have any business license. The family environment and the internal business environment are considered